Педагогічні умови забезпечення рухової активності дітей п’яти років засобами рухливих ігор - Водоп'янова, Вікторія Сергіївна (My University, 2025)
Наукова робота присвячена аналізу проблеми забезпечення рухової активності дітей п’ятого року життя засобами рухливих ігор. Проаналізовано основні наукові підходи щодо специфіки рухової активності, аналізу фізіологічних і педагогічних чинників, які впливають на її забезпечення. Охарактеризовано сутність і зміст основних наукових понять, пов’язаних із досліджуваною проблемою. Розглянуто специфіку забезпечення рухової активності стосовно дітей п’яти років. Розкрито потенціал рухливих ігор як засобу забезпечення необхідного обсягу та рівня якості рухової активності стосовно дошкільників п’яти років. Здійснено діагностику забезпеченості рухової активності дошкільників у процедурі проведення констатувального експерименту. Розроблено критерії і показники, виявлено та теоретично обґрунтовано три рівні забезпеченості рухової активності в дітей п’яти років віку засобами рухливих ігор. Визначено педагогічні умови забезпечення рухової активності дітей п’яти років засобами рухливих ігор та розроблено методичні матеріали на реалізацію кожної із цих умов.
Vodopianova V. S. Pedagogical Conditions for Ensuring the Motor Activity of Five-Year-Old Children by Means of Active Games. Qualification work. Nizhyn, 2025. The scientific work is devoted to the analysis of the problem of ensuring the motor activity of children of the fifth year of life by means of outdoor games. The main scientific approaches to the specifics of motor activity, the analysis of physiological and pedagogical factors that influence its provision are analyzed. The essence and content of the main scientific concepts related to the problem under study are characterized. The specifics of ensuring motor activity in relation to five-year-old children are considered. The potential of outdoor games as a means of ensuring the necessary volume and level of quality of motor activity in relation to five-year-old preschoolers is revealed. Diagnostics of the provision of motor activity in preschoolers in the procedure of conducting a ascertaining experiment are carried out. Criteria and indicators are developed, three levels of provision of motor activity in five-year-old children by means of outdoor games are identified and theoretically substantiated. Pedagogical conditions for ensuring the motor activity of five-year-old children by means of outdoor games are determined and methodological materials are developed to ensure each of these conditions. Keywords: movement, motor activity, motor regime, motor activity, physiological adaptation, motor competence, mobile game, children of the fifth year of life, physical development, relay games.
Keywords: рух; рухова активність; рухова діяльність; рухова компетентність; рухлива гра; фізичний розвиток; ігри-естафети